Unmasking the African Ghost : Theology, Politics, and the Nightmare of Failed States - Orji, Cyril (Book collections on Project MUSE., 2022)
Africa is continuously redefining itself in the face of Eurocentrism, misery, and oppression. Unmasking the African Ghost is a theological exploration of why the political and economic systems of so many African countries have failed and a proposal for paths toward renewing the social order.